Exploring women's interpretations of survey questions on pregnancy and pregnancy outcomes: cognitive interviews in Iganga Mayuge, Uganda - Doris Kwesiga; Mats Malqvist; Christopher Garimoi Orach; Leif Eriksson; Hannah Blencowe; Peter Waiswa (BMC, 2024)
Abstract Background In 2021, Uganda's neonatal mortality rate was approximately 19 deaths per 1000 live births, with an estimated stillbirth rate of 15.1 per 1000 total births. Data are critical for indicating areas where deaths occur and why, hence driving improvements. Many countries rely on surveys like Demographic and Health Surveys (DHS), which face challenges with respondents' misinterpretation of questions. However, little is documented about this in Uganda. Cognitive interviews aim to improve questionnaires and assess participants' comprehension of items. Through cognitive interviews we explored women's interpretations of questions on pregnancy and pregnancy outcomes. Methods In November 2021, we conducted cognitive interviews with 20 women in Iganga Mayuge health and demographic surveillance system site in eastern Uganda. We adapted the reproductive section of the DHS VIII women's questionnaire, purposively selected questions and used concurrent verbal probing. Participants had secondary school education and were English speaking. Cognition was measured through comparing instructions in the DHS interviewers' manual to participants' responses and researcher's knowledge. A qualitative descriptive approach to analysis was undertaken. Results We report findings under the cognitive aspect of comprehension. Some questions were correctly understood, especially those with less technical terms or without multiple sections. Most participants struggled with questions asking whether the woman has her living biological children residing with her or not. Indeed, some thought it referred to how many living children they had. There were comprehension difficulties with long questions like 210 that asks about miscarriages, newborn deaths, and stillbirths together. Participants had varying meanings for miscarriages, while many misinterpreted stillbirth, not linking it to gestational age. Furthermore, even amongst educated women some survey questions were misunderstood. Conclusions Population surveys may misclassify, over or under report events around pregnancy and pregnancy outcomes. Interviewers should begin with a standard definition of key terms and ensure respondents understand these. Questions can be simplified through breaking up long sentences, while interviewer training should be modified to ensure they thoroughly understand key terms. We recommend cognitive interviews while developing survey tools, beyond basic pre-testing. Improving respondents' comprehension and thus response accuracy will increase reporting and data quality.